Synthesis and Characterizations of Hydroxyapatite from Bovine Bone Using Alkaline Hydrolysis Method - Nuning Aisah; Muslim Efendi Harahap; Dwi Budianto; Mirza Wibowo; Mohammad Dachyar Effendi; Jan Setiawan; Seto Roseno; Dwi Gustiono (Universitas Lampung, 2018)
In this research, the synthesis of hydroxyapatite compound (HAp) has been done by extracting technique from cow cortex thigh bones to eliminate organic compounds contained in bone so that it can be used as raw material of bone graft. The method used is alkaline hydrolysis method of soaking bone in NaOH solution with variation of concentration (1M, 2M, 3M) and immersion time (30 minutes, 60 minutes, 90 minutes). The extracted HAp powder was then analyzed using FTIR, XRD and SEM. The results showed that a hydroxyapatite powder with a soaking time of 30 minutes and a 2M and 3M NaOH concentration did not contain organic elements. The XRD peak pattern shows the phase formed is a hydroxyapatite with a hexagonal structure having an average crystal size of 10-12 nm.